Pengaruh Injeksi Multi Antigen terhadap Pertambahan Berat Badan, Bobot Organ Relatif dan Profil Eritrosit pada Puyuh Jantan (Coturnix coturnix japonica) Usia 5 Bulan - Daryanti, Edhita Putri; Santosa, Koekoeh; Farajalla, Achmad; Maheswari, Hera (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2020)
Coturnix coturnix japonica is one of quail the promising commodities to breding. Health management of poultry in livestock such as quail has problems related to the threat of disease from the environment. Diseases caused by disease agents attack birds resulting in morbidity and mortality so that farmers experience losses. This study aims to determine the effect of injection of two different antigens at different time frames on body weight gain, relative organ weight and erythrocyte profile in 5-month-old male quail. The study used an experimental method of completely randomized design (RAL) with animals as many as 28 male quails divided into 7 groups with 4 replications, namely K0: not injected with antigen, P1: injection SDMD 2%, P2: SDMD injection 2% and ND vaccine, P3 : injection ND and SDMD 2% in week 4, P4: injection vaccine ND, P5: injection SDMD 2% and SDMD 2%, P6: injection treatment ND vaccine and injection ND vaccine. Data obtained by body weight gain, relative organ weight, erythrocyte count, hemoglobin level and hematocrit value. Data were analyzed by Analysis of Variance (ANOVA) using MiniTab17. The results showed that organ weight gain, relative organ weight, heart, heart, pancreas, kidney, lung, spleen, erotrocyte count, hemoglobin level, and hematocrit value were not significantly different (P> 0.05) with control treatment so it can concluded that the effect of antigen injection does not affect the weight gain of organs, the relative weights of the liver, heart, pancreas, kidney, lungs, spleen, the number of erotrosites, hemoglobin levels, and hematocrit values.